2021
DOI: 10.1021/acs.jpclett.1c02230
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Circular Dichroism Responses with High Sensitivity and Enhanced Spectral Resolution in Multipolar Plasmonic Modes of Silver Nanoparticles with Dimensions between 90 and 200 nm

Abstract: Characteristic features of magnetoplasmonic responses in higher-order multipolar (quadrupolar and octupolar) modes of Ag nanoparticles (from 90 to 200 nm in diameter) are demonstrated for the first time using magnetic circular dichroism (MCD) spectroscopy. In optical extinction spectra, with an increase in the size of the nanoparticles, the red shift of dipolar plasmon peaks and the appearance of higher-order multipolar resonances can reasonably be observed. Aside from the dipolar and quadrupolar modes, the oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
(85 reference statements)
0
7
0
Order By: Relevance
“…UV–vis–NIR absorption spectra were recorded using a Hitachi U-4100 spectrophotometer. MCD spectroscopic measurements were carried out using a JASCO J-820 spectropolarimeter equipped with a permanent magnet (PM-491LB) of 1.6 T (tesla) with parallel (+1.6 T) and antiparallel (−1.6 T) fields. , Fourier transform infrared (FT-IR) spectra were recorded using a JASCO FT/IR-550 spectrophotometer by the KBr disk pellet method. The phase structure was examined by using a powder X-ray diffraction (XRD) instrument (Rigaku Ultima-IV) with Cu Kα radiation (λ = 1.5405 Å).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…UV–vis–NIR absorption spectra were recorded using a Hitachi U-4100 spectrophotometer. MCD spectroscopic measurements were carried out using a JASCO J-820 spectropolarimeter equipped with a permanent magnet (PM-491LB) of 1.6 T (tesla) with parallel (+1.6 T) and antiparallel (−1.6 T) fields. , Fourier transform infrared (FT-IR) spectra were recorded using a JASCO FT/IR-550 spectrophotometer by the KBr disk pellet method. The phase structure was examined by using a powder X-ray diffraction (XRD) instrument (Rigaku Ultima-IV) with Cu Kα radiation (λ = 1.5405 Å).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, linewidths and intensities of the two lower-energy peaks are strongly dependent on the solvent, whereas those of the highest-energy peak are not. Additionally, magnetic circular dichroism (MCD) reveals that the highest-energy peak arises from two interacting polaronic transitions that are close in energy, giving a derivative-like spectrum. On the basis of not only the spectroscopic behaviors but also the defective center analysis using X-ray photoelectron spectroscopy (XPS), we propose a new mechanism to account for the NIR polaronic transitions from the viewpoint of bulk or surface polarons.…”
Section: Introductionmentioning
confidence: 99%
“…Several exciting results have been presented in the past decade, enriching the field of magnetoplasmonics with a wide library of material combinations, ranging from pure noble metals or ferromagnetic metal nanostructures , to hybrid multilayered nanostructures made of either noble metals and ferromagnetic moieties. More recently, also plasmonic transparent conductive oxide nanocrystals and nonmagnetic or magnetic hyperbolic nanostructures have been reported to exhibit magnetoplasmonic modulation. Fascinating correlations between localized plasmons and the magneto-optical response at the excitonic resonance have also been reported in doped semiconductor nanocrystals. To date, among homogeneous nanostructures, plasmonic ferromagnetic metal nanostructures exhibit the highest magnetoplasmonic modulation .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, noble metals exhibit higher quality factors due to their reduced losses and sharper resonances. Nevertheless, their modulation is still weak at relatively low magnetic fields (of the order of 1 T). Even if such a response is predicted to linearly increase with the applied magnetic field, ultrahigh magnetic fields are needed to achieve the large magnetoplasmonic response of ferromagnetic nanodisks. Such large fields are hardly achievable with common laboratory-scale equipment, but the experimental analysis of their effect may broaden the understanding of magnetoplasmonic phenomena, thus enabling novel and efficient strategies for future applications.…”
Section: Introductionmentioning
confidence: 99%
“…The A -term is nonzero only when the excited state involved in the transitions is degenerate and is characterized by a derivative line shape. , It has recently been demonstrated that when a semiconducting material such as chalcopyrite has an IB of states that lies in close proximity to the edge of the VB, its nanodots can exhibit visible-frequency negative real permittivities that give rise to DR, enabling a plasmon-like optical behavior in the visible range. Hence bands 3 and 4 can be associated with the DR feature. Note that when characterizing the A -term, absorption bands 3 and 4 are merged into a single band [ 3 + 4 ] as shown in Figures a and c . In the quasi-static DR mode, despite the absence of free carriers in the nanostructures, the negative permittivity is induced by transitions of bound electrons , which is the analogy of the plasmonic metal nanoparticles .…”
Section: Resultsmentioning
confidence: 99%